Small fuel cell powered unmanned aerial vehicle - Tanoko Ardi, Dennise. (2011)
Fuel cell is an attractive option for UAV power plant because of its high specific energy that may potentially increase the endurance by more than five times that of conventional UAVs. Medium fuel cell UAVs (with mass greater than five kg and wing span greater than three m) have been the focus of many works performed in this area of study leaving small fuel cell UAVs (weighing less than two kg) with relatively low attention.